Physical layer security of relay selection NOMA wireless systems - LUO Yancui; LI Guangqiu; YE Mingzhu; GAO Hui; ZHANG Yajuan (Dianxin kexue)
Aiming at poor performance of physical layer security (PLS) of decode-and-forward cooperative non-orthogonal multiple access (NOMA) systems and its performance deterioration in the presence of multi-eavesdropper, the PLS model of multi-relay selection NOMA wireless systems using modify-and-forward (MF) protocol was proposed. The approximate expressions of secrecy outage probability(SOP) and asymptotic SOP of multi-relay selection MF-NOMA wireless systems with non-colluding or colluding eavesdropping scenarios were derived by using Gauss-Chebyshev Quadrature theorem. The simulation results verify the accuracy of PLS performance analysis of the above MF-NOMA wireless systems. The results also indicate that the PLS performance of multi-relay selection MF-NOMA wireless systems will be improved when the number of relays increases or the number of eavesdroppers decreases, and that colluding eavesdropping is more detrimental to secure transmission of multi-relay MF-NOMA wireless systems than non-colluding eavesdropping.